Systematic significance of leaf epidermal characterictics in Shorea Roxb. (Dipterocarpaceae) in Malaysia - Che Amri, Che Nurul Aini; Talip, Noraini (2019)
The taxonomic problems in Shorea mostly involve identification and classification. The investigation presented in this study aims to prove that leaf epidermal characteristics have taxonomic value in Shorea. Epidermal peels were prepared using Jeffrey’s solution. The underside of the leaf surface was scraped with a razor blade to remove lose cells and soaked for several days in Jeffrey’s solution or bleaching agent Vortex. The cleared leaf was washed, stained with Safranin, dehydrated, mounted, photographed and observed as described. For observation under scanning electron microscope, 3 to 5 mm2 leaf sections were washed in water, dehydrated through an alcohol series, were then placed between two glass slides, undergone critical point drying process, coated with gold palladium and were examined in a 2.7Å field emission of Cambridge Instruments Stereoscan 360 scanning electron microscope. Results have shown that the epidermis of the leaf surface under LM is useful for distinguishing S. isoptera, and S. maxwelliana, from the others and also between these two species themselves, so that it could be a diagnostic character. The study of the epidermal surfaces revealed a number of important micromorphological characters, and these characters exhibit interesting interspecific variations that are of significance for species identification and authentification. The presence of crustose wax with an abundance of flakes on the leaf surface may be characteristic of S. parviflora. The epidermal sculpturing has considerable diagnostic value, and may characterize some species and could serve as a criterion of distinguishing S. bracteolata. Results have shown that leaf epidermal features could be useful for authentification and identification purposes especially at species level, thus this study have shown taxonomic value of leaf epidermal characteristics in Shorea.